Effect of the ethanolic extract of Bidens pilosa L. on colon cancer induced in rats - Arroyo, Jorge (2008)
Objectives: To determine the influence of Bidens pilosa L. whole plant ethanolic extract on colon cancer induced in rats. Design: Experimental study. Setting: Faculties of Medicine, Pharmacy and Biochemistry and Biologic Sciences, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biologic material: Holzmann rats. Interventions: Fortyeight 2 months 100 g to 130 g Holtzmann rats were separated in six groups of eight each and 1,2-dimethylhidrazine induction of colon cancer was performed. Groups were normal control, group with pathology and groups with pathology and treatments. Main outcome measures: Nitric oxide levels, oxidative stress markers and colon cellular pattern modifications. Results: There was increment of nitric oxide levels and lipoperoxidation in the 1,2-dimethylhidrazine (DMH) animals, and decrease in those receiving both the toxic and the plant extract. Histopathology revealed cellular disorganization, undifferentiated and invasive adenocarcinoma with DMH; non-dose dependent cytoprotection was evident with treatments, especially with 50 mg/kg. Findings may be due to whole extract flavonoids and phenolic compounds contained in the whole extract that may play an important role in both oxidative stress and anticarcinogenic tumor growth inhibition. Histology details could be diagnostic characteristics useful to verify the vegetable powdered species identity. Conclusions: Under experimental conditions the ethanolic extract of Bidens pilosa L. whole plant presented chemoprotective effect on colon cancer.